1975
DOI: 10.1246/cl.1975.517
|View full text |Cite
|
Sign up to set email alerts
|

DEHYDRATION AND DSHYDROGENATION OF sec-BUTANOL OVER ZINC PHOSPHATE CATALYST

Abstract: The dehydration and dehydrogenation of sec-butanol were carried out on zinc phosphate catalyst. The catalyst was found to show a very high selectivity for the dehydrogenation, when calcined at 650°C, though it showed a high selectivity for the dehydration when calcined at 300°C. The active sites for the dehydrogenation were confirmed to be basic sites by a poisoning experiment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…ties are two major goals in catalysis research that have so Studies involving cadmium phosphate (15) and zinc phosfar been pursued using a variety of physical techniques inphate (16) have revealed a close relationship between the cluding IR, visible, UV, and Raman spectroscopies, ESR, acidity and dehydrating capacity of the catalyst. On the other ESCA, EXAFS, and XRD, among others.…”
Section: Introductionmentioning
confidence: 99%
“…ties are two major goals in catalysis research that have so Studies involving cadmium phosphate (15) and zinc phosfar been pursued using a variety of physical techniques inphate (16) have revealed a close relationship between the cluding IR, visible, UV, and Raman spectroscopies, ESR, acidity and dehydrating capacity of the catalyst. On the other ESCA, EXAFS, and XRD, among others.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 In addition, the catalytic properties of zinc phosphate have been investigated in hydrocarbon conversion process, such as dehydration/dehydrogenation of sec-butanol and methanol conversion. 7,8 Since the first report on the synthesis of microporous zinc phosphates, 9 various techniques, including a solid-state reaction 10 and a polyol-mediated approach, 11 have been investigated for the synthesis of monodispersed and nonagglomerated zinc phosphate nanoparticles. A solid-state reaction is a simple room temperature process, but it requires very long reaction time (from several hours to several days) for the fabrication of zinc phosphate nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies carried out on catalysts active in dehydrogenation showed that the activity is favored by the presence of basic sites at the surface of the catalyst. On the contrary, dehydration is often explained by the presence of acid sites [1][2][3][4][5]. 228 LEGROURIetal.…”
Section: Introductionmentioning
confidence: 99%